En-Bloc Excision of the High-ligated Inferior Mesenteric Vein Pedicle With the Specimen in Patients Undergoing Minimally Invasive and Open Sphincter Saving Rectal Resections for Cancer. Issue 1 (February 2019) - Bilgin, Ismail Ahmet; Aytaç, Erman; Baca, Bilgi; Benlice, Çigdem; Aghayeva, Afag; Esen, Eren; Göksel, Süha; Tayfun, Karahasanog[Combining Breve]lu; Hamzaoglu, Ismail
Abstract : Although high-ligated pedicle of the inferior mesenteric artery is usually kept in the resected specimens, the value of preserving high-ligated pedicle of the inferior mesenteric vein within the resected specimens of the sphincter saving rectal resections for cancer is not well defined. In the current study, patients undergoing open, laparoscopic, and robotic sphincter saving rectal resection for cancer were prospectively included. Lymph node invasion and presence of lymph nodes along the IMV pedicles were analyzed. In total 100 patients were included. There were lymph nodes in 63 patients at the IMV and 71 patients at the IMA pedicles. En-bloc removal of the high-ligated IMV pedicle with the resected specimen significantly increased the number of harvested lymph nodes( P <0.001) regardless of surgical modality ( P =0.36). Although it increases the number of harvested lymph nodes with acceptable operative morbidity, no oncological benefits were found related to preservation of high-ligated pedicle of the inferior mesenteric vein within the resected specimen of the rectum.